Identification and expression profiling of GAPDH family genes involved in response to Sclerotinia sclerotiorum infection and phytohormones in Brassica napus - Xu, Jing; Wang, Rongbo; Zhang, Xiong; Zhuang, Wei; Zhang, Yang; Lin, Jianxin; Zhan, Penglin; Chen, Shanhu; Lu, Heding; Wang, Airong; Liao, Changjian (Frontiers in Plant Science, 2024)
Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) is a crucial enzyme in glycolysis, an essential metabolic pathway for carbohydrate metabolism across all living organisms. Recent research indicates that phosphorylating GAPDH exhibits various moonlighting functions, contributing to plant growth and development, autophagy, drought tolerance, salt tolerance, and bacterial/viral diseases resistance. However, in rapeseed (Brassica napus), the role of GAPDHs in plant immune responses to fungal pathogens remains unexplored. In this study, 28 genes encoding GAPDH proteins were revealed in B. napus and classified into three distinct subclasses based on their protein structural and phylogenetic relationships. Whole-genome duplication plays a major role in the evolution of BnaGAPDHs. Synteny analyses revealed orthologous relationships, identifying 23, 26, and 26 BnaGAPDH genes with counterparts in Arabidopsis, Brassica rapa, and Brassica oleracea, respectively. The promoter regions of 12 BnaGAPDHs uncovered a spectrum of responsive elements to biotic and abiotic stresses, indicating their crucial role in plant stress resistance. Transcriptome analysis characterized the expression profiles of different BnaGAPDH genes during Sclerotinia sclerotiorum infection and hormonal treatment. Notably, BnaGAPDH17, BnaGAPDH20, BnaGAPDH21, and BnaGAPDH22 exhibited sensitivity to S. sclerotiorum infection, oxalic acid, hormone signals. Intriguingly, under standard physiological conditions, BnaGAPDH17, BnaGAPDH20, and BnaGAPDH22 are primarily localized in the cytoplasm and plasma membrane, with BnaGAPDH21 also detectable in the nucleus. Furthermore, the nuclear translocation of BnaGAPDH20 was observed under H2O2 treatment and S. sclerotiorum infection. These findings might provide a theoretical foundation for elucidating the functions of phosphorylating GAPDH.